Percepción de las Mujeres durante la Gestación, Parto y Puerperio de la comunidad Cuatro Esquinas durante el periodo agosto -noviembre 2021 - Pilamunga Hinojoza, Maria Teresa (2022)
Purpose: To know the life stories about the experiences of women during pregnancy, childbirth, and the puerperium, emphasizing the perceptions of care practices, knowledge, and customs that pregnant women and puerperal women resort to throughout the reproductive process, in the Cuatro Esquinas community, during the period August-November 2021. Methodology. Qualitative study of a phenomenological type, an interview consisting of 14 reflection questions was used with 12 women in pregnancy, childbirth and postpartum stages, whose interview data were qualitatively analyzed in the Atlas Ti software, determining six core categories; my feelings, complications and remedies, my changes, expectations, my surroundings, my life advice. Results: the women state that they have experienced strong feelings such as sadness and joy at the same time, although they have not received family support in the most representative moments, they have had to overcome physical difficulties and discomfort and socioeconomic problems. The greatest desire in any situation they faced was to see their son or daughter healthy, to show love, affection, tenderness and above all care, they always managed the faith in God being their greatest protective entity. Conclusions: it was possible to identify favorable perspectives in care practices during the stages of pregnancy, childbirth and postpartum. Keywords: care, pregnancy, childbirth, postpartum, perspective, experiences.